Myocardial Infarction: Etiology, Pathophysiology, And Modern Management Approaches - Turdiyev, Mavlonbek; Xojimatov, Dilshod; Yusufjonov, Jasurbek; Qodirov , Iqboljon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
Myocardial infarction (MI) remains one of the leading causes of morbidity and mortality worldwide, primarily resulting from acute occlusion of coronary arteries and subsequent myocardial ischemia. The incidence of MI continues to rise due to lifestyle changes, aging populations, and the prevalence of cardiovascular risk factors such as hypertension, diabetes mellitus, dyslipidemia, obesity, and smoking. The pathophysiology of MI involves atherosclerotic plaque rupture, platelet aggregation, thrombosis, and subsequent myocardial necrosis, which triggers inflammatory and neurohormonal responses that influence cardiac remodeling and patient outcomes [1][2]. Clinical manifestations of MI vary, ranging from typical chest pain, dyspnea, and diaphoresis to atypical presentations such as fatigue, syncope, or silent infarction, particularly in elderly patients and those with diabetes [3][4]. Early diagnosis is critical and is guided by electrocardiography, cardiac biomarkers (troponins, CK-MB), and imaging modalities such as echocardiography and coronary angiography [5][6]. Management strategies for MI include immediate reperfusion therapy, either via percutaneous coronary intervention (PCI) or thrombolytic therapy, alongside pharmacologic management with antiplatelet agents, anticoagulants, beta-blockers, ACE inhibitors, statins, and other adjunct therapies [7][8]. Secondary prevention emphasizes lifestyle modifications, risk factor control, cardiac rehabilitation, and adherence to guideline-directed medical therapy [9][10]. Recent research has focused on biomarker discovery, risk stratification tools, and novel pharmacologic agents to improve outcomes and reduce post-MI complications such as heart failure, arrhythmias, and recurrent ischemic events [11][12]. This article reviews the etiology, pathophysiology, clinical features, diagnostic modalities, and contemporary management of myocardial infarction, highlighting the importance of early intervention, comprehensive care, and patient-centered approaches for optimal outcomes.